Inflammatory Indicators and Radiological Features of Vertebral Column Weaving Craftsmen - Indri Seta Septadina; Rulan Adnindya; Tri Suciati; Hanna Marsinta Uli (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Static sitting conditions in the weaving craftsmen for a long time can cause negative effects in terms of health, especially in musculoskeletal complaints such as muscle pain, spinal pain, and cramps. Complaints of musculoskeletal disorders need to be treated well because if the pain is left it can spread to the extremities, and increase the risk of other diseases. This study was conducted to determine the effects of musculoskeletal disorders (MD) on weaving craftsmen in Palembang to radiologic features of the vertebral column, and inflammatory indicators. The research is an observational analytic study with a cross-sectional design. The population of this research is 30 public weaving craftsmen in Palembang. The variables studied were age, working time, radiologic features by X-Ray examination. Low Back Pain (LBP) was identified from a Nordic questionnaire whereas other factors were measured using a self-data questionnaire. Data were analyzed using the Chi-square method. The results of the analysis of the difference in low back pain based on radiological images (X-ray) found that there was no significant difference between the mean low back pain scores based on the radiological picture (p-value = 0.641) P> ?. The results of the correlation analysis of low back pain with degrees of disability found that there was no significant correlation between low back pain with CRP (p-value = 0.780) p> ?, with a Correlation Coefficient (r) = -0.53 meaning the strength of the correlation between low back pain with SRT category is very weak with negative correlation direction.